The Correlation Between Bronchopulmonary Dysplasia and Platelet Metabolism in Preterm Infants - Yan, Longli; Ren, Zhuxiao; Wang, Jianlan; Xia, Xin; Yang, Liling; Miao, Jiayu; Xu, Fang; Gao, Weiwei; Yang, Jie (Frontiers in Pediatrics, 2021)
Background：Platelets play an important role in the formation of pulmonary blood vessels, and thrombocytopenia is common in patients with pulmonary diseases. However, few studies have reported on the role of platelets in bronchopulmonary dysplasia. Objective: To explore the relationship between platelet metabolism and bronchopulmonary dysplasia in premature infants. Methods: A prospective case-control study was performed in a cohort of premature infants (born with a gestational age less than 32 weeks and a birth weight less than 1500 grams) from 1 June 2017 to 1 June 2018. Subjects were stratified into two groups according to the diagnostic of bronchopulmonary dysplasia: with bronchopulmonary dysplasia (BPD group) and without bronchopulmonary dysplasia (control group). Platelet count, circulating megakaryocyte count (MK), platelet activating markers (CD62P and CD63), thrombopoietin (TPO) were recorded and compared in two groups on the 28 day after birth, then, serial thrombopoietin levels and concomitant platelet counts were measured in infants with BPD. Results: A total of 252 premature infants were included in this study. 48 premature infants developed BPD, 48 premature infants without BPD in the control group who were matched against the study infants for gestational age, birth weight, and admission diagnosis at the age of postnatal day 28. Compared to the controls, infants with BPD had significantly lower peripheral platelet count[BPD vs controls: 180.3 (24.2) x 109/L vs 345.6 (28.5) x 109/L, p=0.001], Circulating MK count in the BPD group was significantly more abundant than that in the control group [BPD vs controls: 30.7 (4.5) /mL vs 13.3 (2.6) /mL, p=0.025], The level of CD62p, CD63 and TPO in BPD group were significantly higher than control group [29.7 (3.1)% vs 14.5 (2.5)%，15.4(2.0)% vs 5.8(1.7)%，301.4 (25.9) pg /mL vs 120.4 (14.2) pg/mL，all P < 0. 05], furthermore, the concentration of TPO was negatively correlated with platelet count in BPD group with thrombocytopenia. Conclusions: Our findings suggest that platelet metabolism is involved in the the development of BPD in preterm infants. Thrombopoietin may be the major regulator in thrombocytopoiesis and platelet homeostasis of infants with BPD.